Aspects concerning the implementation of the nursing care systematization: descriptive study - Lidiane Grutzmacher Azeredo; Rosângela Marion da Silva; Ana Valéria Della Giustina; Ana Amélia Antunes Lima (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
The following descriptive study aimed to identify the factors that ease and make difficult the implementation of the Nursing Care Systematization in two wards of a university hospital. The collection of data happened from September to October 2008 applying a survey to 16 nurses. The data analysis was supported by the tool Statistical Package for the Social Sciences. The results showed the way factors that ease the implementation of systematization in specific meetings approaching the topic and the desire for professional practice change. As examples of shortcoming factors, it is possible to point the performance of nursing itself and the lack of time. Due to the data, it is suggested the bound of other forms of dialogue that enable a sharper discussion of the uncertainties pointed by the nurses in order to help them conduct the nursing care systematization.